Safeguarging Children: An All Encompassing Alternative - S. Saidu, Oluwaseun; Oguntola, Mulkat A. (Online Journal of Research in Islamic Studies, 2015)
There is a clamour world over for the need to safeguard children from abuse, neglect cum other forms of maltreatment and to promote their welfare. The advocates of this notion believe that this need arises because children are vulnerable, need care and support and their welfare is paramount especially in the early years of life because events in those years go a long way in shaping their future. While the authors agree with this proposition, they disconcur with the widely accepted approach to safeguarding which considers such causes as largely exogenous, curative, and largely independent of spiritual underpinnings but more or full of a physical exercise. Employing incisive Ã‚â€œtheoreticsÃ‚â€ and analysing revealing case studies, the study tries to educate the parental as well as filial audience by presenting the true idea of safeguarding from an Islamic perspective perhaps it will go a long way in shaping the prevalent notion of safeguarding which is fast gaining grounds amongst Muslims and non-Muslims alike.